Charge transport and molecular diffusion within self-assembled nanostructures - Ghimire, Govinda (Kansas State University, 2019)
This dissertation describes charge transport behavior within redox-active block copolymer (BCP) microdomains and the diffusion behavior of charged dye molecules within self-assembled bolaamphiphilic organic nanotubes (ONTs) of different surface charge and inner diameters. In-depth understanding of the charge transport efficiency within redox-active microdomains in electrode-supported BCP thin films is crucial for their various electrochemical applications. Similarly, understanding of the diffusion behavior of differently charged dye molecules in ONTs will help design nanotubular materials better suited for drug-delivery and adsorbent applications. In the former study, polystyrene-block-poly(2-(acryloyloxy) ethylferrocenecarboxylate) (PS-b-PAEFc) of different PAEFc volume fractions (fPAEFc) was used as redox-active BCPs. The AFM images of PA-b-PAEFc thin films suggested that the morphology of PAEFc microdomains was dependent of the volume fraction. A series of electrochemical data revealed that thin films based on large fPAEFc, which were expected to yield lamellar and cylindrical microdomains, afforded redox-active microdomains that extended from the underlying electrode to the film–solution interface. In addition, charge transport efficiency, which was represented by apparent diffusion coefficient, within the ferrocene-containing microdomains was similar irrespective of fPAEFc, reflecting the similar concentration and dynamic properties of the redox-active moieties. Furthermore, the charge transport was observed in an acetonitrile solution but not in an ethanol solution, indicating that the thin films needed be swollen for redox-mediated charge propagation across the ferrocene moieties in the microdomains. Interestingly, the thin films rendered redox-active in the ethanol solution upon applying an oxidative potential in the acetonitrile solution, possibly due to the migration of electrolyte ions into the films, albeit with lower charge transport efficiency. The “activated” gold-supported PA-b-PAEFc thin films were applicable as electrochemically responsive heterogenous catalysts for Michael addition reaction between a β-dicarbonyl compound and an enone in an ethanol solution. Importantly, the efficiency of the catalytic reaction could be regulated by the potential application, and its selectivity reflected the permeability of the reactants through the thin films. In the latter study, the diffusion behavior of differently charged fluorescent molecules within individual ONTs was systematically measured using imaging fluorescence correlation spectroscopy (imaging FCS) at different pH and ionic strength conditions. The ONTs with the inner diameters of 10 or 20 nm, which were self-assembled from asymmetrical bolaamphiphiles, had glucose moieties on their outer surfaces, and amine or carboxyl groups on their inner surfaces. Imaging FCS could be used to measure the diffusion of dye molecules that interacted with nanotube inner surfaces. Indeed, diffusion coefficients of dye molecules within the ONTs were much smaller than those in an aqueous solution and were strongly controlled by electrostatic interactions with the amine or carboxyl groups on the inner surfaces as shown by the pH dependence of the diffusion coefficients. In contrast, effects of ionic strength were relatively minor, suggesting the involvement of non-coulombic interactions in the molecular diffusion. Importantly, imaging FCS data revealed that the diffusion coefficients were independent of ONT length, implying that the properties of the ONTs were uniform in terms of solute loading and release.
Keywords: Charge transport; Nanostructures; Redox; Molecular diffusion